Remnants of Origen's Lost Exegesis of Ecclesiastes in the Commentaries of Jerome and Olympiodorus of Alexandria - Celia, Francesco (Augustinianum, 2025)
Origen's Homilies and Excerpta on Ecclesiastes (Hier., ep. 33, 4) are lost, but a number of scholia are ascribed to him in some catenae. In several cases, the authenticity of these scholia is substantiated by their similarity to the comments of later exegetes who certainly read and were influenced by Origen, in particular Jerome and Olympiodorus. This paper focuses on a selection of ten alike segments of Jerome's and Olympiodorus' Commentaries on Ecclesiastes, provides an annotated list of about twenty further parallels between these, and argues that their resemblance is due to their dependence on Origen. In this manner, this study aims to unearth lost pieces of Origen’s exegesis of Ecclesiastes, to help outline the features of one of his lost works on it, likely the Excerpta, and to highlight the Origenian legacy in later exegetes.